Evaluación del estado nutricional en niños de 1 a 5 años de edad atendidos en el hospital Zumba, del cantón Chinchipe. Año 2015 - Reyes Matailo, Jessica Lorena (2016)
This research work was aimed to determine the assessment of nutritional status of children. The research design was cross-sectional, retrospective, descriptive, and bibliographic field. For information techniques direct observation and survey with observation guide and questionnaire instruments respectively to the parents of 150 children who formed the sample was applied. The results indicated the assessment of nutritional status in weight / age with 73.33%, nutritional status is normal size / age average 60.00%, nutritional status weight / height which is more prevalent with normal being considered 58.67%. Factors influencing the nuticional been found are: exclusive breastfeeding until 6 months with 43.33%, education level of parents bachellerato level with 18.66%, perception of income is good with 53.33%, four meals a day consuming children with 50% power consumed daily is a carbohydrate with 84%, age of onset of complementary feeding in children with 80%, has disease presented with the EDA in their last 5 months with 43.33%. The author educational activities, open house where the types of healthy food for children exposed and eventually became home to mothers of children was held visits. It was concluded that the nutritional status of children aged 1 to 5 years 73.33% is normal, however, he found 14% with severe malnutrition, moderate malnutrition 7.33%; that the main causes are; EDA with 43% and 30% pneumonia.